Energy and infrastructural development of the arctic regions of the Russian federation - Nikiforov, Alexander Alexandrovich; Nikiforova, Vera Dmitrievna; Aksenova, Zhanna Aleksandrovna; Rodionov, Dmitriy; Kompaniitseva, Oksana; Makarenko, Evgenii (Edelweiss Applied Science and Technology, 2025)
The Russian Arctic has vast resource potential, and developing this is a strategic task for the country. Energy and infrastructure development is of great importance for this territory, as is any other. The plans for large-scale "redevelopment" of the hydrocarbon resource potential of the Arctic regions of the Russian Federation largely determine the relevance of the problem under consideration, taking into account the impact of climate change factors and globalization, followed by technological, organizational, economic, political, and institutional changes, the complete and systemic understanding of which is still in the formation stage. The article reviews the results of scientific research and discussions on such aspects of sustainable development of the Arctic regions of the Russian Federation as energy supply, renewal of transport infrastructure, creation of conditions for intensifying the implementation of investment and innovation projects, and preservation of ecosystems. This study aims to analyze, summarize, and review the established approaches presented in the domestic and foreign economic literature to solve specific scientific and practical problems in the selected areas. The authors used an institutional approach to the subject of the study, relying on historical, statistical-economic, monographic, and abstract-logical methods, as well as the process of expert evaluations. The scientific novelty of the study is the determination of the degree of study of the problems under consideration, as well as the formulation of the authors' position regarding the strengthening of the influence of institutional factors on the implementation of strategic programs for the development of the fuel industry in the Arctic zone of the Russian Federation in turbulent conditions, overcoming the "trap of technological backwardness" through innovative projects of environmental orientation in the oil and gas sector, related energy and transport infrastructure. The main conclusions are based on scientific literature, statistical and analytical data from Rosstat, Rosnedra, and current regulatory and legal documents of the Russian Federation and foreign countries.